BMC Gastroenterology - Bellentani, Stefano
BMC Gastroenterology is an open access, peer-reviewed journal that considers articles on all aspects of the prevention, diagnosis and management of gastrointestinal and hepatobiliary disorders, as well as related molecular genetics, pathophysiology, and epidemiology.